Kultura organizacyjna jako stymulator zmian w Sądeckim Urzędzie Pracy w Nowym Sączu - Iwan, Cecylia (My University, 2012)
Przedmiotem pracy jest analiza kultury organizacyjnej w Sądeckim Urzędzie Pracy w Nowym Sączu oraz jej wpływ na proces zarządzania zmianami. Kultura organizacyjna jest często powiązana z procesem zmian zachodzących w instytucji. Może wpływać pozytywnie na proces zmian tj. ułatwić i wspierać wprowadzanie rozwiązań lub negatywny, tj. utrudniać proces zmian. Badanie przeprowadzone wśród pracowników urzędu miało na celu ustalenie zależności zmian zachodzących w instytucji od kultury organizacyjnej. Jako narzędzie badawcze zastosowano ankietę na temat zmian i kultury organizacyjnej. Przeprowadzone badania dowodzą, że kultura organizacyjna jest determinantem zmian zachodzących w Sądeckim Urzędzie Pracy w Nowym Sączu. Wyniki badań wskazują, że w Sądeckim Urzędzie Pracy mamy do czynienia z kulturą sformalizowaną, opartą na procedurach.

The subject of the presented work is an analysis of the organizational culture in the Office of Empolyment in Nowy Sacz and its influence on the process of management of changes. The organizational culture is often connected with a process of changes that occur in an institution and it can affect this process positively, i.e. by facilitating and supporting implementation of new solutions or negatively, i.e. by making the process difficult. A survey conducted among employees of the Office aimed at establishment of a relationship between changes occur in an institution and the organizational culture. As a researching tool a questionnaire about changes and organizational culture has been applied. Conducted survey proves that the organizational culture is a determinant of the changes occur in the Office of Empolyment in Nowy Sacz. Findings indicate that in the Office of Empolyment in Nowy Sacz we deal with the formalized culture which is based on the procedures.
The organizational culture as a stimulus for changes in the Office of Empolyment in Nowy Sacz
Keywords: kultura organizacyjna; zarządzanie zmianami; organizational culture; management of changes